Water intake of laying hens after exposure to a warm climate - Hamid, Ramlah; Sykes, A. H. (Taylor & Francis, 1979)
1. The water intake of laying hens was measured after exposure for 4 h to an ambient temperature (TA ) of 35 or 40 °C.